The mediating role of coping strategies between depression and social support and the moderating effect of the parent–child relationship in college students returning to school: During the period of the regular prevention and control of COVID-19 - Wang, Jing; Chen, Yu; Chen, Huimin; Hua, Long; Wang, Jun; Jin, Yuelong; He, Lianping; Chen, Yan; Yao, Yingshui (Frontiers in Psychology, 2023)
OBJECTIVE According to the WHO, compared to before the COVID-19 pandemic, young people showed a significant increase in depressive symptoms. In light of the recent coronavirus pneumonia pandemic, this study was conducted to determine how social support, coping style, parental relationships, and depression are associated. We investigated how these factors interacted and affected the prevalence of depression during this challenging and unheard-of time. Our research may help both individuals and healthcare professionals better comprehend and assist those who are coping with the pandemic's psychological effects. DESIGN AND MAIN OUTCOME MEASURES 3763 students from a medical college in Anhui Province were investigated with Social Support Rate Scale, Trait Coping Style Questionnaire, and Self-rating Depression Scale. RESULTS when the pandemic situation was normalizing, social support was associated with depression and the coping style of college students (P＜0.01). During the period of pandemic normalization, the parent-child relationship moderated the relationship between social support and positive coping (t=-2.45, P＜0.05); the parent-child relationship moderated the relationship between social support and negative coping (t=-4.29, P＜0.01); and the parent-child relationship moderated the association between negative coping and depression (t=2.08, P＜0.05). CONCLUSION Social support has an impact on depression in the period of the regular prevention and control of COVID-19 through the mediating role of coping style and the moderating effect of the parent-child relationship.